Laboratory manual: practical biology BIO0401 - Zahari, Shafiyyah Solehah; Hamzah, Haliza; Teruk, Kamaril Azlah; Mohd Nasohah, Nor Sa'adah; Mohd Sani, Rositi Mashani (IIUM Press, International Islamic University Malaysia, 2018)
This is the Laboratory Report Practical Biology BIO0401 for Practical Biology course. Practical Biology is one of the courses offered by the Department of Biology, CFS IIUM. This laboratory report is intended for students to develop laboratory techniques and skills at the foundation level. The skills are required for the students to have the ability to carry out experiments and present findings scientifically and also to prepare and equip the students to pursue their study at the undergraduate level. This laboratory manual is organized into ten chapters. The experiments are designed to enhance students' knowledge and understanding of biology and biological issue thus the experiments are related to topics in Biology 1 and Biology 2 courses.